Subakromiyal impingement sendromunda farklı egzersiz programlarının karşılaştırılması - Çelik, Derya (My University, 2005)
This study was conducted at Marmara Medical School, Department of Physical Medicine and Rehabilitation between February and August 2004. Thirty patients who had subacromial impingement syndrome were enrolled in the study. The goal of the study was to evaluate the effects of the two different exercise programs on subacromial impingement syndrome. Patients were randomly allocated into two groups, each group consisting of 15 patients. The first group performed 90° and below 90° wand exercises, stretching of the posterior capsule, internal rotation exercises and strengthening of the rotator cuff. The second group performed 90° and above 90° wand exercises, stretching of the posterior and inferior capsule and internal rotation exercises. Both of the groups were also treated using intermittent ultrasound, transcutaneus electrical stimulation and cold pack. The subjects were treated for two weeks (10 sessions) and evaluated by Constant score, Beck Depression Scale, Visual Analog Scale, face scale, physican / therapist global assessment and patients' global assessment before the treatment, immediately after the treatment, 2 and 14 weeks after the treatments. Range of motion was measured by goniometry as well. As a result, mean flexion values of the second group were found to be greater than those of the first group. In addition, VAS score was better in the firt group than that in the second group immediately after the treatment. The other measurements were not found to be significantly different between the two groups.
Keywords: Fiziksel Tıp; Rehabilitasyon